GAMBARAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA DI WILAYAH KERJA PUSKESMAS SAYURMATINGGI KECAMATAN SAYURMATINGGI KABUPATEN TAPANULI SELATAN TAHUN 2023 - Rangkuti, Nur Aliyah; Harahap, Cory Linda Futri; Rangkuti, Juni Andriani; Harahap, Mei Adelina; Nasution, Ayannur; Ritonga, Nefonavratilova; Ramadhini, Delfi; Yuni Aflah; Deliana Tarigan (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Anemia is a condition where the hemoglobin (Hb) level in the blood is less than normal, based on age group, gender and pregnancy. Anemia in pregnancy causes hemoglobin levels below 11 gr% in the first and third trimesters or hemoglobin levels <10.50 to 11.00 gr/dl. Anemia is an important factor in pregnancy because it is associated with morbidity or mortality in the mother and fetus. Anemia in pregnancy is a problem because it reflects the socio-economic welfare of society and has a huge influence on the quality of human resources. Anemia in pregnant women is called "potential danger for mother of child" (potentially dangerous for mother and child) which is why anemia requires serious attention from parties involved in health services. This research aims to find out the picture. The research was conducted in the Sayurmatinggi Health Center Working Area, Sayurmatinggi District, South Tapanuli Regency in 2023. The method in this research was descriptive. The population in the study was 56 pregnant women. The sample in this study was 55 using total sampling technique. The research results showed that the research results showed that the level of knowledge was poor for 26 people (46.4%), sufficient for 18 people (32.1%) and good knowledge for 12 people (21.4%). Advice for pregnant women is expected to recognize the danger signs of pregnancy early, especially in pregnant women, such as anemia and know how to prevent it.